The Effect of Learning Gamelan Art on Emotional Intelligence - Jarmani Jarmani (Institute of Computer Science (IOCS), 2022)
Adolescents are increasingly confronted with emotional issues, demanding a solution such as adolescent emotional intelligence development. Traditional Indonesian music, notably Javanese gamelan, can help adolescents develop emotional intelligence. People who follow a set of rules and limits undertake Javanese gamelan exercises. When practicing gamelan, the individual must hit his gamelan tool and listen to the gamelan played by his colleagues in the gamelan group to generate a harmonic gamelan sound. The study's findings revealed a link between the severity of Javanese gamelan music training and emotional intelligence, with the higher the intensity of Javanese gamelan music training, the higher the emotional intelligence. The intensity variable of Javanese gamelan music training can contribute 30.25 percent to the emotional intelligence variable. In contrast, the remaining 69.75 percent is influenced by elements other than the intensity variable of Javanese gamelan music training. Beyond the intensity variables of Javanese gamelan music training, the family, non-family, physical, and psychological environments all have a role.